(untitled) (International Journal of Engineering and Computer Science, 2015)
Advancement in technology has made things simpler and easier for mankind. Automatic systems are being preferred over manual system. This research work presents the development of SIM300 GSM-module controller for smart homes. The system allows the user to monitor electrical equipment via the mobile phone set by sending commands in the form of SMS messages and receiving the appliance status, as the feedback. The main aim of this prototype is to reduce electricity wastage, provide security and replace human work force, which is prone to errors to automated system. The system will be integrated with microcontroller and SIM300 GSM module network interface using assembly language. It is activated when a user sends the SMS to the controller, on receiving the SMS command, the microcontroller unit then automatically controls the electrical appliances by switching “ON” or “OFF” the device according to the user instruction. The design technique used in this research is top down decomposition; the approach is best-suited when the problem and its environment are well defined.